Adherence to Dietary Approaches to Stop Hypertension (DASH) Dietary Pattern in Relation to Chronic Obstructive Pulmonary Disease (COPD): A Case–Control Study. (3rd October 2017) - Ardestani, Mohammad Emami; Onvani, Shokouh; Esmailzadeh, Ahmad; Feizi, Awat; Azadbakht, Leila
ABSTRACT: Objective : This case–control study was designed to investigate the association between adherences to the Dietary Approaches to Stop Hypertension (DASH) diet in patients with chronic obstructive pulmonary disease (COPD) in comparison to subjects without COPD. Design : This is a case–control study. Usual dietary intake was assessed using a validated food frequency questionnaire. Lung function was evaluated with spirometry testing, and one of the researchers inquired about other respiratory symptoms, including chronic cough, sputum, and breathlessness. Adherence to the DASH dietary pattern was assessed according to the Fung method. Setting : This study was conducted at Alzahra University Hospital of Isfahan, Iran, in 2015. Subjects : Eight-four patients with COPD and 80 subjects without a history of COPD participated in study. Results : The mean age of participants was 57 years. Average smoking in the case group was about 27.5 pack-years. Spirometry tests including forced expiratory volume in 1 second (FEV1 ), forced vital capacity (FVC), and FEV1 /FVC were significantly lower in patients with COPD ( p = 0.0001). Among COPD symptoms, cough was significantly decreased across tertiles of DASH score ( p = 0.03). Significant differences were found for DASH score between patients with COPD and control subjects (19.82 + 3.63 vs 21.13 + 3.82, p = 0.02). Vitamin C, vitamin E, and dietary fiber intake were lower in patients with COPD (144.32 + 70.51 vs 166.97 + 71.88, p = 0.04, 7.49 + 3.91 vs 8.72 + 3.21, p = 0.02 and 19.34 + 7.05 vs 22.19 + 7.87, p = 0.01, respectively). Conclusion : We observed that adherence to a DASH dietary pattern among patients with COPD was significantly lower compared to the control group. Cough was significantly decreased by increments in adherence to a DASH dietary pattern.